Vacuum impregnation for β-carotene retention in mango prior to solar drying - Fratta, Michela; Viola Salvador, Paula; Davidsson, Henrik; Gomez Galindo, Federico ; 0000-0003-4994-8073 (AIMS Agriculture and Food, 2025)
Vacuum impregnation (Ⅵ) is a versatile processing technique that enhances the nutritional and functional properties of fruits and vegetables by infusing bioactive compounds into their porous structures. This study demonstrates the utility of Ⅵ for fortifying fresh mango with β-carotene, a critical nutrient for addressing vitamin A deficiency, and for mitigating nutrient loss during solar drying. Fresh mango slices were impregnated with β-carotene emulsions prepared using homogenization at two different pressures and were then dried under controlled solar simulation conditions. Ⅵ increased β-carotene content in mango tissue from an average of 10.5 ± 2.3 ppm (control) to 20.4 ± 1.1 ppm or 24.0 ± 6.6 ppm depending on homogenization pressure, demonstrating effective nutrient incorporation. The emulsion's particle size distribution had no measurable impact on impregnation efficiency (p < 0.05), as the particle size was compatible with the mango's porous microstructure. Despite significant β-carotene degradation due to solar drying (p < 0.05), the β-carotene levels in the impregnated dried mangoes (9.4 ± 3.9 ppm and 12.6 ± 4.3 ppm) remained close to those in untreated fresh mangoes. This result highlights Ⅵ's potential to produce dried mango products that retain essential nutrients even under challenging drying conditions. In regions like sub-Saharan Africa, where vitamin A deficiency affects millions and post-harvest mango losses are as high as 40%, this approach offers a dual solution: improving nutritional outcomes and reducing food waste. The study also positions Ⅵ as a cost-effective, scalable technology for developing countries, with implications for reducing malnutrition, supporting economic livelihoods, and enhancing the utilization of abundant local fruit resources. Future research will focus on in-situ trials with freshly harvested mangoes and optimization of solar drying methods to further validate this strategy and enhance its scalability.